No effects of rhythmic visual stimulation on target discrimination: An online alpha entrainment experiment. (15th October 2021) - de Graaf, Tom A.; Duecker, Felix
Abstract: Previous research established that rhythmic sensory stimulation can affect subsequent stimulus perception, possibly through 'entrainment' of oscillations in the brain. Alpha frequency is a natural target for visual entrainment, because fluctuations in posterior alpha oscillations have been linked to visual target detection or discrimination. On the other hand, alpha oscillations also relate to attentional mechanisms, such as attentional orienting or selection. Previous visual alpha entrainment studies focused on differential processing of targets presented in‐phase with the preceding rhythmic stimulation relative to out‐of‐phase targets (an 'SOA effect'), putatively related to the phase of entrained neuronal alpha oscillations. Fewer studies probed the consequences of rhythmic alpha stimulation for attention mechanisms related to alpha power. Here, we asked whether alpha stimulation of one hemifield has similar effects on reaction times as we see for increased alpha synchronization in magneto/electroencephalography (M/EEG) studies (i.e., more alpha means impaired processing and functional inhibition). We implemented a task inspired by attention studies, assessing reaction times to ipsilateral vs. contralateral visual targets, with and without concurrent presentation of distractors. Yet, in place of any attention cues, we presented a rhythmic, vs. arrhythmic, alpha‐frequency train of visual flashes to one hemifield, in a large sample size ( N = 115) in an online experiment. We found clear evidence that flash train rhythmicity did not impact task performance. We also found that the spatial congruence between the unilateral flash train and the subsequent visual target did impact response times but only in the presence of contralateral distractor stimuli. We discuss implications, limitations and future directions. Abstract : Rhythmic visual stimulation at alpha frequency ('entrainment') has previously led to modulated visual processing over SOAs, implying entrained alpha‐phase effects. What about alpha power? We here found no differential effects of rhythmic as compared with arrhythmic stimulation in a reaction time task inspired by attention studies, aiming to test whether rhythmic alpha stimulation might modulate attention‐related alpha power.